Explosibility Safety Factor: An Approach to Assess Mine Gas Explosion Risk - Cheng, Jianwei; Luo, Y.; Zhou, F. (2015)
The determination of explosibility is critical for mine rescues or controlling the severity of a mine accident, especially for the gas explosion event. After a severe coal mine fire or an explosion event, a common practice for minimizing the risk is to seal the related area, and then to inject the inert gas (N2 and/or CO2) into the sealed area to extinguish the fire and prevent potential explosions. At the same time, rescue works will be immediately planned. In order to avoid the risk associated with a potential secondary explosion, the rescue workers are not allowed to go underground until the atmosphere of the sealed area no longer has the possible explosibility. Therefore, mining engineers must precisely know how dangerous the current situation is and what is the risk degree. One explosibility method, the Coward explosibility diagram, can clearly identify the explosive status of a mine atmosphere and track its explosibility trend as the compositions of mine atmosphere change. However, the Coward diagram can only identify the mine gas explosibility, but it lacks the ability showing the safety margin. In this paper, a new concept, explosibility safety factor (SF), is introduced and defined to improve the safety for the rescue works when using the Coward method. It can clearly show how dangerous the current atmospheric status is if the state point locates in any not-explosive zones and also provide a measurement method to scale the safety margin when dealing with the explosibility of a sealed mine atmosphere. Application of this factor is also demonstrated at the end of the paper.